PEMBAGIAN DAN PEMISAHAN KEKUASAAN KETATANEGARAAN DI INDONESIA - S, Laurensius Arliman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The division and separation of powers are fundamental principles in the constitutional system to establish a fair, transparent, and accountable government. In Indonesia, this principle is governed by the 1945 Constitution and was significantly strengthened after its amendments. Executive power is held by the President, legislative power by the House of Representatives (DPR) and the Regional Representative Council (DPD), and judicial power by the Supreme Court, the Constitutional Court, and the Judicial Commission. This system is complemented by a checks and balances mechanism to prevent the dominance of any branch of power. However, its implementation faces challenges, such as overlapping authorities and potential inter-agency interventions. This study aims to analyze the application of the theory of the division and separation of powers in Indonesia, identify existing problems, and propose solutions to enhance the effectiveness of governance.Keywords: Division Of Powers, Separation Of Powers, Constitutional System, Checks And Balances